Dancing Bees, Singing Whales. The Impact of Idiosyncratic Information on Children’s Attitudes Toward and Moral Reasoning About Animals - (:unkn) unknown (My University, 2023)
Research in conservation psychology suggests that the tendency to engage in conservation behaviors develops from the interplay of both knowledge of and affinity toward nature (Schmitz & Rocha, 2018; Berenguer, 2007). The present study explores this connection between knowledge and attitudes by investigating the impact of information on individuals' attitudes and care toward animals. This study focuses on knowledge in the form of idiosyncratic information, due to considerations of potential cognitive strengths as well as the pervasiveness of “fun facts” in everyday life. Idiosyncratic information about natural items is not likely to be found in science textbooks at grade-school level, but a quick Google search will quickly produce a vast array of pages listing facts that will amaze you, surprise you, and “change the way you view the animal kingdom” (Crow, 2020). In the present study, 70 children (ages 4-10) and 45 adults participated in a virtual interview. Their knowledge of and attitudes toward four target animals were assessed before they were provided with taxonomic or idiosyncratic information for each of the target animals. Participants’ attitudes were then measured again to assess whether they had changed as a result of the information provided. Finally. participants were presented with an environmental moral dilemma which involved harm to the target animals. To assess whether the information received impacted care for the target item, participants were asked whether they thought that the harmful actions were permissible or not, and why. The present study tested two major predictions: First, that idiosyncratic facts would enhance participants’ positive attitudes toward animals more than taxonomic facts. Results indicate that, overall, positive attitudes toward a target animal increase after receiving information about it, and that this effect is more pronounced upon learning idiosyncratic than taxonomic facts. Second, we expected idiosyncratic facts to impact participants’ moral reasoning toward animals differently from taxonomic facts. Specifically, we predicted that participants would display higher levels of biocentric reasoning when exposed to idiosyncratic than to taxonomic information. Results do not support this hypothesis; however, they indicate that overall participants made a large use of biocentric justifications. Furthermore, participants who held positive attitudes upon being exposed to idiosyncratic information manifested higher rates of biocentric justifications, suggesting a relationship between attitudes and moral reasoning.
Keywords: conservation psychology; environmental attitudes; idiosyncratic information; moral reasoning